2011
DOI: 10.1016/j.yfrne.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the neural circuit that mediates female sexual receptivity

Abstract: Female sexual behavior in rodents, typified by the lordosis posture, is hormone-dependent and sex-specific. Ovarian hormones control this behavior via receptors in the hypothalamic ventromedial nucleus (VMH). This review considers the sex differences in the morphology, neurochemistry and neural circuitry of the VMH to gain insights into the mechanisms that control lordosis. The VMH is larger in males compared with females, due to more synaptic connections. Another sex difference is the responsiveness to estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 183 publications
(235 reference statements)
0
60
1
1
Order By: Relevance
“…The VMHvl has a pivotal role in female sexual behavior (12,35), and the ARC is thought to be essential in the negative feedback actions of estrogen (31,44,45). Importantly, ARC neurons are prime sensors of the internal environment integrating metabolic and reproductive functions (9,23).…”
Section: Discussionmentioning
confidence: 99%
“…The VMHvl has a pivotal role in female sexual behavior (12,35), and the ARC is thought to be essential in the negative feedback actions of estrogen (31,44,45). Importantly, ARC neurons are prime sensors of the internal environment integrating metabolic and reproductive functions (9,23).…”
Section: Discussionmentioning
confidence: 99%
“…The organization of brain sex differences during this critical period is important for adult reproductive function [1,2]. Studies have shown that administration of estradiol-17β or compounds with estrogenic activity to newborn rats during critical period results in irreversible masculinization as well as defeminization in the brain resulting in abnormal sexual behavior as adults [1,[3][4][5][6]. Recently we observed that neonatal exposure to estradiol-17β in the female rat resulted in up-regulation of COX-2 and increased size of SDN-POA compared to control during adulthood [7].…”
Section: Introductionmentioning
confidence: 99%
“…Higher brain areas are required to mediate the hormonal control of the reflex. In particular, the ventromedial nucleus (VMN) of the hypothalamus is critical for this hormonal control and communicates with the dorsal and lateral portions of the periacqueductal gray (PAG) of the midbrain (Flanagan-Cato, 2011; Kow and Pfaff, 1998). This VMN-PAG information is thought to be critical to estrogen’s ability to facilitate the reflex and to coordinate the behavior with the female’s ability to procreate.…”
Section: 0 Introduction and Overviewmentioning
confidence: 99%